Periodontal Disease and Risk of Bladder Cancer: A Meta-Analysis of 298476 Participants - Xie, Wen-Zhong; Jin, Ying-Hui; Leng, Wei-Dong; Wang, Xing-Huan; Zeng, Xian-Tao; , BPSC investigators (Frontiers in Physiology, 2018)
Objective: It has been reported that the periodontal disease is linked to a number of malignant tumors such as lung cancer and pancreatic cancer. In this study, we aimed to investigate the association of periodontal disease with risk of bladder cancer by a meta-analysis. Methods: PubMed, Scopus, ScienceDirect, and Chinese National Knowledge Infrastructure(CNKI) were searched for eligible publications up to December 15, 2017. Cohort and nested case-control studies on the association between periodontal disease and risk of bladder cancer were included. After study selection and data extraction, pooled hazard ratios (HRs) and their 95% confidence intervals (95%CIs) were calculated using a fixed-effect inverse-variance model. All analyses were performed using the RevMan 5.3 software. Results: Finally, five cohort studies were identified and included in this meta-analysis, involving 1,104 bladder cancer cases and 298,476 participants. Summary estimates based on adjusted data showed that periodontal disease was not significantly associated with the risk of bladder cancer (HR = 1.09, 95% CI = 0.95-1.25, I2 = 0%). A similar result was also observed after cumulative, subgroup and sensitivity analyses. Conclusions: Current evidence from cohort studies suggests that patients with periodontal disease may not be at an increased risk of developing bladder cancer.